Substitutability between drugs, innovation, and fiscal policy in the pharmaceutical industry - de Mello-Sampayo, F.; Vale, S.; Camões, F. (Annals of Economics and Finance, 2015)
A theoretical model is developed in order to examine and explain the growth and welfare effects of fiscal policies in the pharmaceutical industry. When the fiscal instrument is a tax over pharmaceutical firms' profits, R&D by firms in the pharmaceutical sector results in growth if there is a generic market. Otherwise, a subsidy over pharmaceutical firms' profits should be considered to generate innovation in medicines. In terms of policy implications, our empirical results suggest that stimulating generic competition in the pharmaceutical sector is a main instrument to contain costs and promote welfare.